MAC OS X Snow Leopard pocket guide - Seibold, Chris (O'Reilly Media, 2009)
Whether you're new to the Mac or a longtime user, this handy book is the quickest way to get up to speed on Snow Leopard. Packed with concise information in an easy-to-read format, Mac OS X Snow Leopard Pocket Guide covers what you need to know and is an ideal resource for problem-solving on the fly. This book goes right to the heart of Snow Leopard, with details on system preferences, built-in applications, and utilities. You'll also find configuration tips, keyboard shortcuts, guides for troubleshooting, lots of step-by-step instructions, and more. Learn about new features and changes since t.